2011
DOI: 10.1186/1465-9921-12-73
|View full text |Cite
|
Sign up to set email alerts
|

A promoter SNP rs4073T>A in the common allele of the interleukin 8 gene is associated with the development of idiopathic pulmonary fibrosis via the IL-8 protein enhancing mode

Abstract: BackgroundInterleukin-8 (IL-8) is a potent chemo-attractant cytokine responsible for neutrophil infiltration in lungs with idiopathic pulmonary fibrosis (IPF). The IL-8 protein and mRNA expression are increased in the lung with IPF. We evaluated the effect of single nucleotide polymorphisms (SNPs) of the IL-8 gene on the risk of IPF.MethodsOne promoter (rs4073T>A) and two intronic SNPs (rs2227307T>G and rs2227306C>T) of the IL-8 genes were genotyped in 237 subjects with IPF and 456 normal controls. Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 28 publications
1
35
0
3
Order By: Relevance
“…Interestingly, increased IL-8 levels were also found in the BAL of patients with IPF (Willems et al, 2013), and polymorphism in the IL-8 gene has been linked to IPF (Ahn et al, 2011). It was recently speculated that COPD and IPF may be "distinct horns of the same devil" (Chilosi et al, 2012).…”
Section: B Transient Receptor Potential Channels Inmentioning
confidence: 99%
“…Interestingly, increased IL-8 levels were also found in the BAL of patients with IPF (Willems et al, 2013), and polymorphism in the IL-8 gene has been linked to IPF (Ahn et al, 2011). It was recently speculated that COPD and IPF may be "distinct horns of the same devil" (Chilosi et al, 2012).…”
Section: B Transient Receptor Potential Channels Inmentioning
confidence: 99%
“…Nevertheless, some studies highlighted the fact that IPF patients with a high TGF-β1 producing genotype are incline to have a worse prognosis and a more rapid deterioration in lung function (Arkwright et al, 2000;Alhamad et al, 2013). A single nucleotide polymorphism (rs4073T N A) was also recently found in the promoter of the CXCL8 gene and was significantly associated with higher BALF CXCL8 concentrations and an increased risk of development of IPF in humans (Ahn et al, 2011). Existence of such polymorphism in CIPF dogs has not yet been investigated.…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…Therefore, the aim of the present study was to compare basal circulating blood concentrations of four molecules of interest obtained in healthy dogs from seven breeds differently predisposed to CIPF. Selection of molecules studied was based on their potential implication into the pathogenesis of canine pulmonary fibrosis in view of data from either human or canine literature and were as follows: the chemokine (C-X-C motif) ligand 8 (CXCL8) (Cui et al, 2010;Ahn et al, 2011;Krafft et al, 2013), the chemokine (C-C motif) ligand 2 (CCL2) Moore, 2014), the serotonin (5-HT) (Konigshoff et al, 2010;Krafft et al, 2013), and the vascular endothelial growth factor (VEGF) (Ando et al, 2010;Woodcock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased IL8 con centrations in bronchoalveolar lavage correlated with decreased FEV1 values [8]. The IL8 (-251T>A) variant was also associated with an increased risk of idiopathic lung fibrosis [38]. A study from China showed that IL8 variants can contribute significantly to COPD risk in residents of regions with high air pollution levels [39].…”
Section: Discussionmentioning
confidence: 97%